2012
DOI: 10.1002/jbio.201200069
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of zebrafish brain development using optical coherence tomography

Abstract: The zebrafish is a well-established model system used to study and understand various human biological processes. The present study used OCT to investigate growth of the adult zebrafish brain. Twenty zebrafish were studied, using their standard lengths as indicators of their age. Zebrafish brain aging was evaluated by analyzing signal attenuation rates and texture features in regions of interest (ROIs). Optical scattering originates from light interaction with biological structures. During development, the zeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Development of brain morphology has been visualized with OCT in small animal models, such as Xenopus [122], zebrafish [40, 123] and fetal mouse [124]. Basic structures of the early embryonic brain, including diencephalic ventricles, midbrain and hindbrain, were revealed within 24 hours post fertilization in zebrafish [40].…”
Section: Oct Imaging In Development Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Development of brain morphology has been visualized with OCT in small animal models, such as Xenopus [122], zebrafish [40, 123] and fetal mouse [124]. Basic structures of the early embryonic brain, including diencephalic ventricles, midbrain and hindbrain, were revealed within 24 hours post fertilization in zebrafish [40].…”
Section: Oct Imaging In Development Biologymentioning
confidence: 99%
“…Basic structures of the early embryonic brain, including diencephalic ventricles, midbrain and hindbrain, were revealed within 24 hours post fertilization in zebrafish [40]. Morphology progression of more sophisticated brain structures including the olfactory bulb, telencephalon, cerebellum, medulla, tectum opticum and optic commissure, were visualized in adult zebrafish using OCT [123, 125, 126], showing progression of brain morphology. Optical attenuation in zebrafish brain was quantified, demonstrating a negative linear correlation between optical signal attenuation and brain aging [123].…”
Section: Oct Imaging In Development Biologymentioning
confidence: 99%
“…However, most of the work was performed by using early-stage zebrafish [21]. More recently, two cases were reported that could capture part of the features of adult zebrafish brain based on OCT [22,23]. However, due to the slow imaging speed and limited penetration depth, a comprehensive in vivo 3D characterization of the whole adult zebrafish brain has never been accomplished.…”
Section: Introductionmentioning
confidence: 99%
“…OCT has been used to image various biological processes in zebra fish (Danio rerio), e.g. brain growth (Lin et al, 2013), and eye structure (Divakar Rao et al, 2006). Recently, OCT has been used to image tissue structure in previously frozen krill samples (Bellini et al, 2014) to a depth of c. 2 mm, with a resolution of c. 12 μm.…”
Section: Optical Coherence Tomography (Oct) Is a Non--invasive High-mentioning
confidence: 99%